Digital video broadcasting – terrestrial-interface design - Tan, Zheng Lin. (2011)
With the advancement in technology, IPTV has been one of the fastest growing technology sectors. As analog signals are rapidly being replaced by digital signals for television shows, Digital Video Broadcasting (DVB) became more popular. DVB has many different kinds of standards for digital TV. In Singapore, DVB-T (Terrestrial) is used. It is used in Singapore to broadcast free-to-air channels such as digital 5, 8 and ChannelNewsAsia (CNA).